The kill order - Dashner, James 1972- (New York Delacorte Press, 2012)
"Mark struggles to make sense of his new, post-disaster world in this prequel to The Maze Runner"--
Prequel to: The maze runner
1 12
Keywords: Natural disasters -- Fiction; Science fiction; Survival -- Fiction; Virus diseases -- Fiction